EFFICIENT PROTOCOL FOR MICROPROPAGATION OF HIGH PSORALEN YIELDING CHEMOTYPE OF CULLEN CORYLIFOLIUM (L.) MEDIK.- A TRADITIONAL HERB OF IMMENSE MEDICINAL VALUE - SIVA K. CHETRI,; KULDEEP SHARMA,; SHAHNAZ SUBHAN,; VEENA AGRAWAL, (International Journal of Pharma and Bio Sciences, 2014)
Cullen corylifolium (L.) Medik. is a traditional herb of immense medicinal value. In vitro micropropagation of an elite chemotype of C. corylifolium was achieved using nodal explants employing different growth regulators (BA, Kn and 2iP). BA at 5 µM proved optimum to differentiate the maximum average number of multiple shoots. Indirect regeneration via caulogenesis from the two month old cultures of nodal explants was achieved when subcultured on B5 medium containing BA, 2iP or Kn. BA at 10 µM BA proved most effective with an average of 12.33 shoots per culture. The frequency of in vitro shoot formation enhanced markedly by the addition of adjuvants, viz. Ad.S. or CW along with optimum level of BA. Rhizogenesis of in vitro shoots was achieved on half strength MS basal medium and 97% plants survived after field transfer. Genetic and biochemical fidelity of the in vitro regenerants was established through RAPD and HPLC analysis, respectively.